The extracellular matrix of the lung and airway responsiveness in asthma - F.G. Salerno; M.P. Foschino Barbaro; O. Toungoussova; E. Carpagnano; P. Guido; A. Spanevello (Monaldi Archives for Chest Disease, 2016)
The extracellular matrix is the main determinant of the structure and of mechanical behaviour of the lung. The extracellular matrix is also responsible for the mechanical interdependence between airway and parenchyma due to the alveolar attachments to the airways. Asthma is characterized by bronchial hyperresponsiveness, airway remodelling and inflammation, and an altered extracellular matrix may play a role in all these functional and structural abnormalities. The excessive airway narrowing observed in asthma may be related to the altered viscoelastic properties of lung parenchyma and airway wall, determining a decrease in the mechanical load opposing the airways’ smooth muscle contraction. Indeed, an altered extracellular matrix deposition in asthma in humans, has been demonstrated. In addition, in the asthmatic lung, the matrix seems to contribute to airway inflammation, airway remodelling, and to those alterations of the smooth muscle function of the airway and morphology typical of asthma.